Penguatan Teaching Factory Beras Sehat Melalui Pelatihan Pembuatan Pupuk Organik Berbasis Zero Waste - Jumiatun, Jumiatun; Pertami, Rindha Rentina Darah; Fatimah, Titien; Soelaksini, RR Lilek Dwi; Widodo, Tirto Wahyu (SEJAGAT : Jurnal Pengabdian Masyarakat, 2024)
Rice cultivation activities at Tefa Beras Sehat Polije still depend on the use of inorganic fertilizers. The advantage of inorganic fertilizers is that they decompose faster so that nutrients are absorbed faster by plants (fast release). So that the use of inorganic fertilizers continues to be carried out by farmers. However, dependence on organic fertilizers causes fertilizers to become scarce and their prices to increase. The purpose of this activity is to provide training in making organic fertilizers to the TEFA Beras Sehat Community. This activity took place from September to November 2023. The results of this activity were an 85% increase in skills and knowledge of waste management into organic fertilizers, 20% of partners were aware of the importance of organic fertilizers in environmentally friendly cultivation and 50% of partners had the potential to optimize the use of waste around their homes to become organic fertilizers.